Achieving carbon neutrality in China: Legal and policy perspectives - Wang, Bo; Yu, Junping; Wu, Rui (Frontiers in Environmental Science, 2022)
China has committed to achieve carbon neutrality by 2060. However, this task is considerably difficult. To meet its carbon neutrality commitments, China will rely on a range of policies and laws. By analyzing policies and laws issued at the central and local levels in China from 2019 to the present, we assessed how the Chinese government will achieve its carbon neutrality targets by breaking them down. The results of this study showed that: (1) Carbon neutrality targets are translated into indicators such as energy consumption per unit of GDP, carbon dioxide emissions per unit of GDP, non-fossil energy consumption ratio, forest cover, and forest stock; (2) The focus of policy and law-making is on the role of the government rather than the carbon market; (3) The central government tends to promote and guide low-carbon development through specific actions; (4) Local policy and law-making is less proactive and is influenced by localism; (5) Overall, China's carbon neutrality policies and laws are characterized by comprehensive coverage, with emphasis on the rational use of executive power and the development of low-carbon-related technologies; and (6) The existing policies and laws remain unclear, with low levels of legislation and insufficient public participation. This paper puts forward some suggestions on the introduction of the climate change law, the promotion of citizen participation in policy-making and implementation, and the establishment of a public interest litigation system on climate change.